Bacteriological Quality Assessment of Raw Beef Sold in Sylhet Sadar (The Agriculturists, 2016)
This study was conducted to assess the bacteriological quality of fresh raw beef sold in different markets of Sylhet Sadar. A total of seventy five (75) fresh raw beef samples were randomly collected from seven  major markets (Shibgonj, Mirabazar, Kazitula, Ambarkhana, Madina market, Bandar bazar and Sheikh ghat) of Sylhet Sadar. Total Viable Count of the samples ranged between 2.5 × 105 to 2.25 × 108cfu/g. Acceptability for consumption of these samples as satisfactory, acceptable and rejected were 40, 32 and 28%, respectively. A total of 115 bacterial isolates of 5 genera were identified including gram negative Escherichia coli [15(10%)], Salmonella spp. [20(13.33%)], Klebsiella spp. [30(20%)], Enterobacter spp. [10(6.67%)] and gram positive Staphylococcus spp. [40(26.67%)]. The presence of these organisms in fresh meat from conventional beef is alarming.DOI: http://dx.doi.org/10.3329/agric.v13i2.26654The Agriculturists 2015; 13(2) 09-16